A Qualitative Exploration of Nurses’ Information-Gathering Behaviors Prior to Decision Support Tool Design - Jeffery, Alvin D.; Kennedy, Betsy; Dietrich, Mary S.; Mion, Lorraine C.; Novak, Laurie L. (Applied Clinical Informatics, 2017)
Background: Large and readily-available clinical datasets combined with improved computational resources have permitted the exploration of many new research and clinical questions. Predictive analytics, especially for adverse events, has surfaced as one promising application of big data, and although statistical results can be highly accurate, little is known about how nurses perceive this new information and how they might act upon it. Objectives: Within the context of recognizing patients at risk for cardiopulmonary arrest, this study explored the possibility of incorporating predictive analytics into clinical workflows by identifying nurses’ current information gathering activities and perceptions of probability-related terms. Methods: We used a qualitative description approach for data collection and analysis in order to understand participants’ information gathering behaviors and term perceptions in their own words. We conducted one-on-one interviews and a focus group with a total of 10 direct care bedside nurses and 8 charge nurses. Results: Participants collected information from many sources that we categorized as: Patient, Other People, and Technology. The process by which they gathered information was conducted in an inconsistent order and differed by role. Major themes comprised: (a) attempts to find information from additional sources during uncertainty, (b) always being prepared for the worst-case scenario, and (c) the desire to review more detailed predictions. Use of the words probability, risk, and uncertainty were inconsistent. Conclusions: In an effort to successfully incorporate predictive analytics into clinical workflows, we have described nurses’ perceived work practices for gathering information related to clinical deterioration and nurses’ beliefs related to probability-based information. Findings from our study could guide design and implementation efforts of predictive analytics in the clinical arena.Jeffery AD, Kennedy B, Dietrich MS, Mion LC, Novak LL. A Qualitative Exploration of Nurses’ Information-Gathering Behaviors Prior to Decision Support Tool Design. Appl Clin Inform 2017; 8: 763–778 https://doi.org/10.4338/ACI-2017-02-RA-0033
Keywords: Qualitative Research; Decision-Making; Computer-Assisted; Nursing